Allogeneic stem cell transplantation following relapse post autologous stem cell transplantation in adult patients with acute myeloid leukemia: A retrospective analysis of 537 patients from the Acute Leukemia Working Party of the EBMT. Issue 12 (26th October 2018) - Christopeit, Maximilian; Labopin, Myriam; Gorin, Norbert‐Claude; Saraceni, Francesco; Passweg, Jakob; Forcade, Edouard; Maertens, Johan; Van Lint, Maria Teresa; Bosi, Alberto; Niederwieser, Dietger; Ehninger, Gerhard; Polge, Emmanuelle; et al.
Abstract : Patients with acute myeloid leukemia (AML) who relapse after autologous stem cell transplantation (ASCT) can be rescued by allogeneic SCT. We identified 537 adult patients with AML allografted in second complete remission (CR2) or first relapse after ASCT in the European Society for Blood and Marrow Transplantation (EBMT) registry. At 3 years post allograft, leukemia free survival (LFS) was 31.4% [95%CI 27.3‐35.6], overall survival (OS) 39.5% [95%CI 35.1‐43.9], relapse incidence (RI) 34.6% [95%CI 30.4‐38.8], and nonrelapse mortality (NRM) 33.7% [95%CI 29.6‐37.9]. RI was higher in patients transplanted in relapse in comparison to those transplanted in CR2 (HR 1.76, P = .004) and in patients who relapsed later after ASCT (HR 0.97 per month, P < 10 −3 ), both translating into better LFS/ OS. Relapse was also lower in patients undergoing allogeneic stem cell transplantation (allo‐HSCT) from an unrelated donor (UD) in comparison to those transplanted from a matched sibling donor (MSD) (HR 0.49, P < 10 −3 ). NRM was increased in patients who received total body irradiation (TBI) pre‐ASCT (HR 2.43; P < 10‐4), translating into worse LFS/OS. LFS/OS did not differ between patients allotransplanted with reduced intensity (RIC) or myeloablative (MAC) conditioning. In conclusion, one third of adult patients with AML relapsing post ASCT can be rescued with allo‐HSCT, with better LFS/OS in patients who relapsed later post ASCT, those transplanted in CR2 and those who had not received TBI pre‐ASCT.